+0

# Let $f$ be defined by $f(x & \text{ if } x \leq 3, \\ -x^3+2x^2+3x & \text{ if } x>3. \end{array} \right.\ 0 43 1 Let f be defined by \[f(x) = \left\{ \begin{array}{cl} 3-x & \text{ if } x \leq 3, \\ -x^3+2x^2+3x & \text{ if } x>3. \end{array} \right.$Calculate $f^{-1}(0)+f^{-1}(6)$.

Guest Sep 23, 2017
Sort:

#1
+76929
+1

$$$f(x) = \left\{ \begin{array}{cl} 3-x & \text{ if } x \leq 3, \\ -x^3+2x^2+3x & \text{ if } x>3. \end{array} \right.$Calculate f^{-1}(0)+f^{-1}(6).$$

f-1 (0)    must mean   that either   3 - x  = 0       or   -x^3 + 2x^2  + 3x  = 0

However......in the second function x = 0    is the only thing that makes this true, but that function isn't defined for x  = 0

So.....it must mean that  3 - x  = 0....and x  = 3......so   f-1 (0)   = 3

And

f-1 (6)  must mean that either   3 - x  = 6      or that    -x^3 + 2x^2  + 3x  = 6

Looking at the second function  we have that

-x^3 +2x^2  + 3x  = 6  →    x^3 -2x^2 - 3x + 6  =  0  →   x^2( x - 2) - 3(x - 2)  = 0  →

(x^2 - 3) (x -2)  = 0  →    x  = ±√3   or x  = 2   are the x values that make this true....but....these values are all < 3  and this function isn't defined for these values

But    3 - x   = 6     when  x  = -3     which is valid

So

f-1 (0)  =  3     and   f-1 (6)  =  -3

So  ....  their sum   = 0

CPhill  Sep 23, 2017

### 22 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details